2009
DOI: 10.1002/pssa.200824326
|View full text |Cite
|
Sign up to set email alerts
|

Phase structure and electrical properties of strontium modified (Na0.48–xK0.48–xLi0.04Srx)Nb0.89Ta0.05Sb0.06O3 ceramics

Abstract: (Na0.48–x K0.48–x Li0.04Srx)Nb0.89Ta0.05Sb0.06O3 (abbreviated as NKLSrx NST) lead‐free ceramics are fabricated by conventional solid state reaction. The material with perovskite structure contains both tetragonal and orthorhombic phases at room temperature when x ≤ 0.02, and it changes into cubic phase gradually as x increases. A second phase KSr2Nb5O15 begins to appear at x = 0.03 and becomes obvious with increasing Sr content. Dielectric studies show that the Sr2+ modification lowers the Curie temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The environmentally friendly lead-free K 0.5 Na 0.5 NbO 3 (KNN) is a classical ferroelectric material with good piezoelectric, dielectric, and ferroelectric properties and high Curie temperature. 4–8 Generally, vacancy defects would appear in KNN during high-temperature ceramic sintering due to the easy volatilization of K and Na elements, making KNN naturally a photochromic material. 9–12…”
Section: Introductionmentioning
confidence: 99%
“…The environmentally friendly lead-free K 0.5 Na 0.5 NbO 3 (KNN) is a classical ferroelectric material with good piezoelectric, dielectric, and ferroelectric properties and high Curie temperature. 4–8 Generally, vacancy defects would appear in KNN during high-temperature ceramic sintering due to the easy volatilization of K and Na elements, making KNN naturally a photochromic material. 9–12…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the (Li, Ta, and Sb) modified NKN compositions have the critical problem: a high loss tangent of 4% at room temperature. [14][15][16] Nevertheless, many researchers have reported that SrTiO 3 (ST) dopants can improve the piezoelectric properties and reduce the loss tangent for NKN ceramics. 17,18 Accordingly, we predict that ST dopants can also reduce the loss tangent for (Na 0.48 K 0.48 Li 0.04 )Nb 0.89 Ta 0.05 Sb 0.06 O 3 ceramics.…”
mentioning
confidence: 99%